Ancestral gene duplication enabled the evolution of multifunctional cellulases in stick insects (Phasmatodea). (April 2016) - Shelomi, Matan; Heckel, David G.; Pauchet, Yannick
Abstract: The Phasmatodea (stick insects) have multiple, endogenous, highly expressed copies of glycoside hydrolase family 9 (GH9) genes. The purpose for retaining so many was unknown. We cloned and expressed the enzymes in transfected insect cell lines, and tested the individual proteins against different plant cell wall component poly- and oligosaccharides. Nearly all isolated enzymes were active against carboxymethylcellulose, however most could also degrade glucomannan, and some also either xylan or xyloglucan. The latter two enzyme groups were each monophyletic, suggesting the evolution of these novel substrate specificities in an early ancestor of the order. Such enzymes are highly unusual for Metazoa, for which no xyloglucanases had been reported. Phasmatodea gut extracts could degrade multiple plant cell wall components fully into sugar monomers, suggesting that enzymatic breakdown of plant cell walls by the entire Phasmatodea digestome may contribute to the Phasmatodea nutritional budget. The duplication and neofunctionalization of GH9s in the ancestral Phasmatodea may have enabled them to specialize as folivores and diverge from their omnivorous ancestors. The structural changes enabling these unprecedented activities in the cellulases require further study. Graphical abstract: Highlights: Phasmatodea endogenously express multiple copies of glycoside hydrolase family 9 (GH9) genes. Some genes form monophyletic, secondarily xylanolytic or xyloglucanolytic clades. Phasmatodea encode true, bifunctional endo-ß-1, 4-xylanases and –glucanases. Phasmatodea encode true, bifunctional endo-ß-1, 4-xyloglucanases and –glucanases. Many plant cell wall polymers are digested into monomers, with implications for insect nutrition and human bioenergy.